2015
DOI: 10.1097/hcr.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Mobile Health Exercise-Based Cardiac Rehabilitation Intervention

Abstract: Adults with IHD were able to use an mHealth program and reported that text messaging is a good way to deliver exercise information. While mHealth is designed to be automated, programs might be improved if content and delivery were tailored to individual needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
(19 reference statements)
1
26
0
Order By: Relevance
“…Patients must also be able to control their exercise intensity when performing the exercises prescribed by their provider. In 2015, a study evaluating the acceptability of mobile health exercise-based cardiac rehabilitation intervention through text messages found that text messaging was useful in motivating patients with ischemic heart diseases to exercise and continue cardiac rehabilitation programs [6]. What was notable in this study was that the average age of the subjects was 60 years and older, suggesting that elderly patients may understand and participate in medical intervention programs through mobile devices.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Patients must also be able to control their exercise intensity when performing the exercises prescribed by their provider. In 2015, a study evaluating the acceptability of mobile health exercise-based cardiac rehabilitation intervention through text messages found that text messaging was useful in motivating patients with ischemic heart diseases to exercise and continue cardiac rehabilitation programs [6]. What was notable in this study was that the average age of the subjects was 60 years and older, suggesting that elderly patients may understand and participate in medical intervention programs through mobile devices.…”
Section: Discussionmentioning
confidence: 81%
“…The accuracy of HR measurements obtained from a smartphone built-in camera was verified using a method that was previously reported [6]. To measure HR, subjects held smartphones in their right hands, putting the tip of their right hand's index finger on the camera on the back side of the smartphone, and held it in place with limited movement for 1 minute.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Participants were male or female adults (with the exception of one study that included only females) 23 predominantly from the U.S., with a few studies being conducted in the United Kingdom, 30,31 Australia, 32 New Zealand, 33 and China. 34 Participants in eight of the 17 studies had an increased BMI, with one study including cardiac rehabilitation patients.…”
Section: Nonrandomized Studiesmentioning
confidence: 99%
“…The reviewed studies lend support to the social validity of mHealth apps for weight management. Evidence is provided for validity indicators related to app use, measured in terms of app acceptability, 44,45 app engagement, 33 and adherence to self-monitoring via the app 35,40,41 ; indicators related to app evaluation, such as likeability, 33 attitude toward app, 34 perceived app usefulness, 32 and ease of use and usability. 31,32 These outcomes were replicated with older patients and staff through qualitative measures.…”
Section: Nonrandomized Studiesmentioning
confidence: 99%